1998
DOI: 10.1164/ajrccm.157.3.9606120
|View full text |Cite
|
Sign up to set email alerts
|

The Chemotactic Activity of Sputum from Patients with Bronchiectasis

Abstract: Persistent polymorphonuclear neutrophil (PMN) recruitment to airway is thought to be an important component of continuing inflammation and progression of chronic destructive lung diseases. Although chemoattractants are required for the PMN to migrate, the nature of the chemoattractants in the airways has not yet been clarified. We therefore investigated the contribution of interleukin-8 (IL-8) and leukotriene-B4 (LTB4) to the chemotactic activity of lung secretions by inhibiting their activity using a monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 19 publications
4
59
1
1
Order By: Relevance
“…However, the studies reported here (using an LTB 4 receptor antagonist) indicate that LTB 4 contributes 30% of the chemotactic drive in these samples during a bacterial exacerbation. This is consistent with recent findings in patients with bronchiectasis and COPD in the stable state [17], again emphasizing the importance of LTB 4 in neutrophil responses to airway disease.…”
Section: Discussionsupporting
confidence: 93%
“…However, the studies reported here (using an LTB 4 receptor antagonist) indicate that LTB 4 contributes 30% of the chemotactic drive in these samples during a bacterial exacerbation. This is consistent with recent findings in patients with bronchiectasis and COPD in the stable state [17], again emphasizing the importance of LTB 4 in neutrophil responses to airway disease.…”
Section: Discussionsupporting
confidence: 93%
“…Further studies after the resolution of the exacerbation may resolve this issue. However, it should be noted that the increased levels of DES and IDES excretion during the exacerbation are similar to those for the CF and Bx patients in the stable state, in whom the neutrophil burden is also markedly increased [25,26], although lung function is better (table 1).…”
Section: Discussionsupporting
confidence: 58%
“…The present data shows evidence of inflammation in the larger airways in patients with COB with a wide range of neutrophil influx (as reflected in the MPO concentration) in response to the chemoattractants IL-8 and LTB 4 which are thought to play a key role in neutrophil recruitment [28]. Elastase activity was absent or low even though these samples are known to contain the enzyme [29] probably due to inhibition by the natural inhibitors, especially SLPI.…”
Section: Discussionmentioning
confidence: 83%